ANALISIS KARAKTER DALAM NOVEL FIFTY SHADES DARKER OLEH EL. JAMES - LUMOWA, MARCELLA MELISSA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Â The research is entitled â€œAnalisis Karakter dalam Novel Fifty Shades Darker oleh EL. Jamesâ€. There are two main problems o be analyzed those are; â€œwhat are characters of the main characters as revealed in Fifty Shades Darkerâ€ and â€œHow is the method of characterization applied in the novelâ€. This research only focuses on the two main characters Anastasia Steele and Christian Grey. The purpose of this research are to identify human characters, to analyze and describe the characterization. In identifying characters, the writer used Robertsâ€™ theory about characters, in analyzing and describing the characterization, the writer used Perrineâ€™s theory about direct presentation and indirect presentation. The result of this research show that there are several human character found in the novel such as Tough, plain, shy, emotional, sensual, firm, fragile, romantic, overt, honest etc. The method of characterization found in this novel can be divided in two types: direct presentation and indirect presentation. Â Keywords: Character analysis, Fifty Shades Darker, Intrinsic Approach.